Lignin-enhanced reduction of structural Fe(III) in nontronite: Dual roles of lignin as electron shuttle and donor. (15th August 2021) - Sheng, Yizhi; Dong, Hailiang; Kukkadapu, Ravi K.; Ni, Shuisong; Zeng, Qiang; Hu, Jinglong; Coffin, Ethan; Zhao, Simin; Sommer, Andre J.; McCarrick, Robert M.; Lorigan, Gary A.
Abstract: Lignin is a major component of plant-derived soil organic matter (SOM) in soils and sediments. Fe-bearing clay minerals are widely distributed in these environments and often co-exist with lignin. While previous studies have reported the electron shuttling and donating roles of certain redox-active SOM in the dissimilatory reduction of structural Fe(III) in Fe-bearing clay minerals, the role of lignin in this process remains unknown. Here we studied this role by incubating an Fe-rich smectite (nontronite NAu-2) with two types of lignin (soluble and insoluble) in the absence and presence of an Fe(III)-reducing bacterium Shewanella putrefaciens CN32 under anaerobic condition. Lactate was added in some experiments as an extra electron donor. The results demonstrated that both soluble and insoluble lignins abiotically reduced structural Fe(III) in NAu-2. The reduction extent was proportional to lignin concentration. After abiotic reaction, lignin served as either electron shuttle or electron donor in the presence of CN32: (1) When lactate was present, lignin served as an electron shuttle to enhance the rate of Fe(III) reduction; (2) When lactate was absent, lignin served as an electron donor for Fe(III) reduction. Although the ultimate biotic Fe(III) reduction extents were similar in the presence of either soluble or insoluble lignin, the reduction rates with soluble lignin were higher than those with insoluble lignin, likely owing to their different electron transfer mechanisms. After interaction with NAu-2 and/or CN32, soluble lignin structure largely remained intact, but with some decreases of humic/fulvic acid-like and protein-like compounds, aromatic functional groups (e.g., CH, CO, COOH), and aliphatic/aromatic compounds. An increase of semiquinone-like organic radicals was observed after lignin interaction with NAu-2. These chemical changes of lignin were likely coupled with the reduction of structural Fe(III) in nontronite. Upon reduction, the nontronite did not display much dissolution and mineral transformation. The findings of this study provide insights into the role of lignin in promoting mineral-microbe interactions and have significant implications for coupled Fe and C biogeochemical cycles in soils and sediments.